(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2023)
In order to become a teacher in general, and a foreign language teacher in particular, one must first possess a certain variety of skills. It is nevertheless impossible to be a teacher without, in fact, having played the role of one. Therefore, it is important to emphasize the importance of initial education and supervised professional practices that should be carried out during university studies with the intention to prepare and familiarize the Spanish language students with the job of a language teacher. In consequence, the aim of this paper is to investigate the percentage of Spanish teachers in Serbia who have completed professional practices during their studies and how they have prepared for their teaching jobs. Through an anonymous questionnaire and an analysis of a sample of 46 SFL teachers, a general dissatisfaction with the practices is first presented, as well as 40% of them who did not even have the opportunity to perform them. In addition to a shortage of opportunities to practice teaching in the workplace, there is also a lack of initiative and awareness about some volunteer opportunities. Therefore, it is considered significant having expanded the knowledge of the subject, especially since it is imperative that teachers receive both theoretical and practical education. It is believed that both observing classes and participating in the process of creating and planning a class or series of classes are quite necessary, considering that respondents highlighted the relationship with their mentors, their advice, and possibilities for collaboration in activities as the most effective.